Comunidade fitoplanctônica e qualidade da água em ecossistemas aquáticos do estado do Ceará - Soares Filho, Aldeney Andrade (2010)
Water is the most important resource for humans, though it s eems there is no concern of human beings in preserving it, because daily activities increasingly under mine the quality of this resource. This study aimed to analyze the phytoplankton community structure and water quality in aquatic ecosystems of Ceará State (Brazil). Monthly collections were made during the rainy and dry seasons between 2004 and 2007 in the following ecosystems: the Cauípe, Mundaú, Ceará and Malcozinhado river estuarie s; the Jijoca, Pecém, Uruaú and Maraponga lakes; the Ipu and Andreas waterspouts and the Favelas, Corte and Campus do Itaperi dams. The results showed significant changes in phytoplankton community structure, mainly influenced by levels of rainfall. The Bacillariophyceae were predominant in the ecosystems studied, except in the Favelas, Corte and Campus do Itaperi dams, which showed high levels of eutrophication, with dominance of Cyanophyceae, Zygnematophyceae and Chlorophyceae, respectively. Rare species, the great majorit y, formed a group totally isolated from those considered dominant, abundant and little abundant, consisting of a small number of species, confirming the major seasonal influence of the region's on the phytoplankton community. Ecosystems showed great variation in diversity, richness and evenness of species, however, diversity was highest during the rainy season. The following environments were classified according to the concentration of dissolved O 2 and CO2, total ammonia, nitrite, phosphate, as well as on trophic status indices of phosphate and/or water transparency and on the presence of bioindicators: the Mundaú, Cauípe and Ceará river estuaries, Maraponga lake and the Favelas, Corte and Campus do Itaperi dams as eutrophic environments; the Malcozinhado river estuary and Pecém and Uruaú lakes as mesotrophic environments; and Jijoca lake and the Ipu and Andréas waterspouts as oligotrophic environment. Several bioindicators of eutrophic and/or polluted waters were recorded, in partic ular the presence of potentially toxic cyanobacteria in various ecosystems, with blooms in the Ceará river estuary and Favelas dam, while significant biomass was not recorded in other environments, even those showing a high trophic status, such as the Campus do Itaperi dam, with a Chlorophyceae bloom, and the Corte dam, with a Zygnematophyceae bloom, showing that the joint analysis of biological and physicochemical parameters of the ecosystem is of paramount importance for an appropriate environmental assessment of the health of aquatic cosystems.